2022
DOI: 10.3389/fneur.2022.815902
|View full text |Cite
|
Sign up to set email alerts
|

Rhino-Orbital Cerebral Mucormycosis in a Patient With Diabetic Ketoacidosis: A Case Report and Literature Review

Abstract: BackgroundRhino-orbital cerebral mucormycosis (ROCM) is a rare, invasive, and fatal fungal disease. Due to the lack of specific clinical manifestations and adequate auxiliary examinations, patients are easily misdiagnosed in the early stage. Early diagnosis and timely therapy are essential for successful treatment.Case ReportWe report a 68-year-old man with diabetic ketoacidosis, presented with orbital apex syndrome (OAS), fever, and pansinusitis, which progressively worsened to death only 4 days after admissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…ROCM is a rare but fatal fungal infection involving the cerebellar and orbital sinuses as proposed by Champion early in 1969. [ 3 ] A sudden and rapid rise in mucormycosis incidence was observed during the second wave of the COVID-19 pandemic. The global prevalence of mucormycosis before the COVID-19 pandemic ranges from 0.005 to 1.7 per million population and it is almost 80 times higher in India (0.14/1000) compared to other world regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ROCM is a rare but fatal fungal infection involving the cerebellar and orbital sinuses as proposed by Champion early in 1969. [ 3 ] A sudden and rapid rise in mucormycosis incidence was observed during the second wave of the COVID-19 pandemic. The global prevalence of mucormycosis before the COVID-19 pandemic ranges from 0.005 to 1.7 per million population and it is almost 80 times higher in India (0.14/1000) compared to other world regions.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] Rhino-orbital-cerebral mucormycosis (ROCM) is the most common clinical presentation of mucormycosis. [ 3 ] Symptoms of ROCM include headache, facial pain, facial/orbital swelling, and/or nasal eschar. Progressive ROCM infection results in necrosis of the head and neck, paranasal sinuses, proptosis of the eyeball, and/or ptosis of the eyelid with possible central nervous system (CNS) involvement.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there are no effective clinical biomarkers for ROCM diagnosis ( Walsh et al., 2012 ; Lass-Florl, 2017 ). Previous studies have revealed that up to 90% of ROCM cases are undiagnosed and untreated ( Walsh et al., 2012 ; Dong et al., 2022 ). In our present case, we obtained a rapid and accurate etiological result within 24 h with the help of a novel technology called mNGS, which has emerged as a fast, precise, and effective laboratory technology.…”
Section: Discussionmentioning
confidence: 99%
“…Mucormycosis, caused by opportunistic pathogenic fungi that belong to the order Mucorales, is a difficult-to-diagnose rare disease with high mortality that commonly occurs in patients with impaired immune status, particularly those with diabetes mellitus, hematological malignancy, and neutropenia ( Dong et al., 2022 ). According to literature review, this is the first reported patient with AML who developed disseminated infection caused by M. indicus ( Supplementary Table S1 ).…”
Section: Discussionmentioning
confidence: 99%